Arthroscopic removal of metal foreign bodies from the knee joint after explosive war injuries - Gulan, Gordan (Array, 2009)
Abstract: The results of arthroscopic removal of metallic fragments from knee joint due to explosive war injuries are presented. In period from 1991–1995 during war in Croatia we have operated 25 knee joints. Indications for arthroscopy were based on radiographic and clinical findings. The foreign bodies in the joint were found in 19 patients while additional 6 had foreign bodies in the periarticular soft tissues. Arthroscopies were performed on average one month after wounding. The foreign bodies were placed in different parts of the joint with no prediction sites. In 8 knees foreign bodies were freely mobile, and in 11 were anchored to different intraarticular structures. There were no complications during early postoperative period as well as in follow up period